A Multimode SiGe BiCMOS 5–6 GHz Front-End IC that Enables 802.11ac Wave 2 and 802.11ax Wireless LAN Front-End Designs. (18th August 2016) - Huang, Chun-Wen Paul; Christainsen, Kenny; Allum, Justin; Lam, Lui; Chen, Andrew; Doherty, Mark; McPartlin, Mike; Vaillancourt, Bill
Abstract : A multimode 4.9–5.9 GHz front-end IC (FEIC) is presented, which is based on SiGe BiCMOS and realized in an 2 x 2 x 0.5 mm3 package. With a 5 V supply, the Tx chain features 31 dB gain and meets -40 dB DEVM for 1024 QAM 802.11ax tests up to 19 dBm Pout and -35 dB DEVM for 256 QAM 802.11ac tests up to 20 dBm Pout. The linearity is perfectly linearly scaled with the supply voltage and insensitive to modulation bandwidths and duty cycle. The low linearity mode with DPD can achieve the similar linear power with 40 mA current reduction. The Rx chain features <2.5 dB NF and 15 dB gain with 7 dBm IIP3 and 8 dB bypass attenuation with 25 dBm IIP3. All the unique features simplify the front-end circuit designs of complex 802.11ac and emerging future complex radios standards.